Power scalability of a single-stage Yb-doped superfluorescent fiber source. (7th January 2016) - An, Yingye; Yu, Yu; Cao, Jianqiu; Huang, Zhihe; Guo, Shaofeng; Chen, Jinbao
Abstract: A high-power all-fiber broadband superfluorescent source is fabricated by using a distributed side-coupled cladding-pumped Yb-doped fiber. It is found experimentally that besides the optical feedback, the active fiber parameters have a significant effect on the power scaling. By optimizing the fiber length, a record amplified spontaneous emission output of 186.3 W is achieved, and the slope efficiency with respect to launched pump power is 78%. The bandwidths are larger than 20 nm. Furthermore, the power scalability of the superfluorescent source is analyzed numerically. The parasitic laser oscillation can be suppressed further with a large core to cladding ratio.